INFLUENCE OF CERTAIN D-METALS ON FORMATION OF ADVANCED GLYCATION END PRODUCTS, AGGREGATION AND AMYLOID TRANSFORMATION OF ALBUMIN IN GLYCATION REACTION - R. A. Litvinov; A. V. Gontareva; L. E. Usmiyanova; D. R. Klimenko (Volgograd State Medical University, Pyatigorsk Medical and Pharmaceutical Institute, 2021)
The aim of the research is to investigate the influence of the factor of the glycation behavior of bovine serum albumin (BSA) by glucose, and the factor of d-metal cations (nickel (II), cobalt (II), iron (II), iron (III), copper (II) or zinc (II)) presence, on the process of aggregation and the amyloid transformation of BSA and, therefore, to establish the effect of these cations on the rate of the formation of advanced glycation end products (AGEs), and the intensity of fluorescence of the amino acids tyrosine and tryptophan.Materials and methods. Reagents in the glycation are: glucose (at the final concentration of 0.36 M), BSA (at the final concentration of 1 mg/ml), deionized water, one of the d-metal cations, i. e. nickel (II), cobalt (II), iron (II), iron (III), copper (II) or zinc (II) (in the form of chloride, sulfate or nitrate salts, at the final concentration of 40 μM). The conditions for the glycation reaction are the incubation for 24 hours at the temperature of 60°C. The influence of two factors (the factor of the glycation reaction and the factor of a d-metal ion presence in the reaction medium) on the concentration of glycation end products (AGEs) formed during the glycation reaction, on the fluorescence intensity of the amino acids tryptophan and tyrosine, on the aggregation of BSA, and on the ability of BSA to the amyloid transformation under the described conditions, have been studied.Results. It was found out that the studied factors have a statistically significant effect on the considered parameters. The highest activity was found for the copper ion (II), which intensifies the formation of the AGEs in the samples where glycation occurs, reduces the fluorescence intensity of the amino acids' tryptophan and tyrosine (independently and increasing the effect against the background of glycation). Besides, it independently causes the aggregation of BSA hereby intensifying the effect against the background of glycation, it independently causes the amyloid transformation of BSA enhancing the effect against the background of glycation. The above-listed effects were the least pronounced in the reaction media with the addition of nickel (II) or cobalt (II). These cations reduce the rate of the AGEs formation, do not cause the formation of protein aggregates. In the presence of glucose, nickel (II) weakly suppresses the fluorescence intensity of tryptophan and tyrosine, and slightly enhances the amyloid transformation of BSA. Cobalt (II) slightly inhibits the amyloid transformation of BSA. In terms of the severity and nature of the effects, the iron (II), iron (III) and zinc (II) cations occupy an intermediate position between copper (II), on the one hand, and nickel (II) and cobalt (II), on the other hand, combining the influence on the AGEs formation, the intensity of fluorescence of tryptophan and tyrosine, the aggregation and amyloid transformation of BSA. In the absence of glucose, the ability of zinc (II) to induce the formation of protein aggregates turned out to be the highest, and its ability to stimulate the amyloid transformation of BSA corresponded to that of copper (II).Conclusion. The presence of d-metal cations affects the rate of the AGEs formation in the glycation reaction, affects the rate of the BSA amyloid transformation and the protein aggregates formation. Among such ions as nickel (II), cobalt (II), iron (II), iron (III), copper (II) and zinc (II), copper (II) ions turned out to be the most active in their ability to accelerate the AGEs formation, suppress the fluorescence of tryptophan and tyrosine, enhance the aggregation and amyloid transformation of BSA in the glycation reaction. The least manifestation of these properties is observed for nickel (II) and cobalt (II) ions.